Utilization of Advanced Computational Methods to Predict Spring-back of Aluminium Alloys in Automotive Industry - Solfronk, Pavel; Sobotka, Jiri; Korecek, David (Manufacturing Technology Journal, 2020)
The automotive industry is one of the most dynamically developing segments of the industrial production worldwide. The introduction of still increasingly stringent emission limits for newly developed cars forces car producers to still reduce the fuel consumption of cars. One option is to use hybrid drive units in combination with a redesign of the automobile body while maintaining the highest possible level of vehicle safety. For these reasons, the automotive industry has been increasingly demanding to apply and process low density (lightweight) alloys, including aluminium-based alloys. These materials are subject to high demands both in terms of mechanical properties and technological workability in the mass production process. The utilization of mathematical modelling (numerical simulations) of production processes is now one of the standards in all phases of design and production the car-body and allows the implementation of variable designs in a relatively short time scale and the detection of potential production problems as well. In this paper, the influence of the kinematic hardening model on the accuracy of spring-back prediction is shown in comparison with the commonly used isotropic hardening model. For deformation analysis, a simple workpiece having ?U-shape? of EN AW 6111 material was used. Such aluminium alloys is used for production car-body panels in the automotive industry. Achieved accuracy of numerical simulation results is evaluated by the comparison shape obtained by numerical simulations and shape of experimentally bended workpiece.
Keywords: Aluminium Alloys; Spring-back; Yield Criterion; Numerical Simulation; Bauschinger Effect